Pengembangan Media Smart Flashcard pada Muatan Pembelajaran IPAS untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V SDN Bandar 03 Batang - Laksana, Bima; Putra, Galih Mahardika Christian (FONDATIA, 2024)
This study carried out has the aim of developing and testing Smart Flashcard learning media in the context of the Science and Social Studies (IPAS) curriculum for fifth-grade students at SDN Bandar 03 Batang. The background of this research is based on the need for a innovative approach in teaching to enhance students' learning outcomes more effectively. Things to home of this research is to evaluate the effectiveness of the Smart Flashcard media in improving students' understanding of complex natural resource materials. The research method involves collaboration with subject matter experts and media specialists in the development process, as well as testing this media with small and large groups of students to obtain valid and reliable data. The findings of this study indicate a rapid improvement in students' learning outcomes, particularly in understanding previously challenging natural resource materials. This research concludes that is the applicatioan of the Smart Flashcard learning media is effective in enhancing students' learning outcomes in the IPAS curriculum. These findings provide a strong foundation for the development of innovative interactive learning media in the future to create a more engaging, interactive, and effective learning environment for students in the learning process.